Comparison of Growth in Three Varieties of the Japanese Extremely Long-Tailed Chicken Breed (Tosa-no-Onagadori) - Ohara, Ken; Takayama, Masahiro; Goto, Tatsuhiko; Osman, Sayed A.M.; Tsudzuki , Masaoki (International Journal of Poultry Science, 2013)
The aim of this study is to reveal whether there are differences in live body weights and growth curves based on Gompertz function among three plumage color varieties (black-breasted white, black-breasted red and white) of the Japanese extremely long-tailed chicken breed (Tosa-no-Onagadori, briefly Onagadori), Special National Natural Treasure of Japan. Body weights were recorded every week from hatching to 30 weeks of age. In males, black-breasted red showed higher values than black-breasted white from 13 to 30 weeks of age. In females, black-breasted red was also higher than black-breasted white in body weights at 17, 19 and 26 to 30 weeks of age. Comparing the earliness of inflection points in growth curves among three varieties, the order was black-breasted white>black-breasted red>white in the female and black-breasted red>black-breasted white>white in the male. The differences in the body weights and inflection points are thought to be due to the genetic background differences between varieties. The information from this study will be useful in developing future strategies for conservation and improvement of the Onagadori as valuable genetic resource.